Mengoptimalkan Layanan Konseling melalui Pemanfaatan Asesmen Psikologi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This article aims to explore ways to optimize counseling services through the utilization of psychological assessments. Psychological assessments are essential tools that can assist counselors in understanding the characteristics, needs, and issues faced by clients. By employing various valid and reliable assessment instruments, counselors can more accurately identify problems and design more effective interventions. Research indicates that appropriate assessments not only enhance the effectiveness of therapy but also expedite the recovery process for clients. Additionally, this article discusses the challenges faced in the implementation of psychological assessments in Indonesia, such as the lack of training for counselors and limited access to quality assessment tools. Recommendations for improving psychological assessment practices in counseling services are also presented, including the need for ongoing training for counselors and the development of assessment tools that are culturally relevant to the Indonesian context. Thus, the optimal utilization of psychological assessments is expected to improve the quality of counseling services and support the psychological well-being of individuals.